(3GdbHIs - (3LGHQ Hf MjGf Hf YHO Gddg Gdchaj, CHh ehSi, J (B200 (3g` s ((3HdOI JHQjR s)
(3ChdgG (B:s
(3GdMeO ddg MeO ef de jcaQ Hg bW bO SHb dfG bHd cJGHfG gPG KeGfjI YTQ cJGHkG s
(3BNQgG (B:s
(3aJYde ef GdQDjI ddTF eG WHYg haYdg heG ajg ef cd hGMO ef GdYfGUQ hgPg bOQI YXjeI s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1421 - (3U(B146s
(3hQO cPdc ai Qbe hgh GdebGdI GdJGSYI YTQ ef cJGH GdSHYjfs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B103 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B105s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B145 s
Keywords: (3GdcjejGA h GdWHjYjGJs